The decision to first enter the public bond market: The role of firm reputation, funding choices, and bank relationships - Hale, Galina; Santos, João A.C. (Journal of Banking & Finance, 2008)
This paper uses survival analysis to investigate the timing of a firm’s decision to issue for the first time in the public bond market. We find that firms that are more creditworthy and have higher demand for external funds issue their first public bond earlier. We also find that issuing private bonds or taking out syndicated loans is associated with a faster entry to the public bond market. According to our results, the relationships that firms develop with investment banks in connection with their private bond issues and syndicated loans further speed up their entry to the public bond market. Finally, we find that a firm’s reputation has a “U-shaped” effect on the timing of a firm’s bond IPO. Consistent with Diamond’s reputational theory, firms that establish a track record of high creditworthiness as well as those that establish a track record of low creditworthiness enter the public bond market earlier than firms with intermediate reputation.